Effect of porous Cu addition on the microstructure and properties of Sn58Bi solder joints. (25th September 2019) - Liu, Yang; Ren, Boqiao; Xu, Ruisheng; Zhang, Hao; Sun, Fenglian
Abstract: In this work, porous Cu (P-Cu) was added into Sn58Bi (SnBi) alloy to obtain a new SnBi@P-Cu composite solder. The microstructure, hardness, shear performance, and thermal conductivity of the solder were investigated in comparison with the eutectic SnBi. Experimental results shows that the addition of porous Cu in the composite solder joint increases the grain size of the β -Sn and the Bi-rich phases in the main area of the solder bulk. The hardness at such area is 292.6 MPa, which is similar with the average hardness of the eutectic SnBi. In some areas enclosed by the Cu pores in the composite solder joint, the solder bulk shows refined microstructure. The average hardness here is 349.3 MPa, which is higher than that of the others. The addition of porous Cu has limited effects on the shear strength of the solder joint. However, it leads to the failure mode transformation of the joint during the shear test. Compared with the eutectic SnBi solder, the thermal conductivity of the Sn58Bi@P-Cu composite solder increases from 22.96 W m −1 · K −1 to 25.90 W m −1 · K −1 due to the addition of the porous Cu.